Characterization of an Unstable Slope Using Geophysical, UAV, and Geological Techniques: Karakoram Himalaya, Northern Pakistan - Khan, Muhammad Younis; Shafique, Muhammad; Turab, Syed Ali; Ahmad, Naseem (Frontiers in Earth Science, 2021)
Given active tectonism, rough terrain and climate, the mountainous ranges in northern Pakistan are prone to geohazards including earthquakes, the unstable slopes and landslides. The frequent land sliding in the region is poses risk to communities, economic activities and transportation network. In this context, the unstable slope above Mayun village calls for a multi-method approach for better assessment of the slope for planning interventions aimed at hazard mitigation. We conducted an integrated study including unmanned aerial vehicle (UAV), and ground penetrating radar (GPR) in coordination with geomorphic field observations to image the possible slip surfaces for a comprehensive understanding of a potential future rockslide with significant socio-economic consequences. UAV derived results helped in delineating the overall extent of the unstable slope and its downslope area in a quick, remote and safe way. GPR profiles have enabled reconstruction of the bedrock’s morphology and its internal structure, and depth distribution of cracks running through the overburden and bedrock. The results provided insight into the stable and unstable compartments of the slope due to thin cover of surficial deposits, high impedance contrast at the overburden-bedrock interface, lateral heterogeneities, and presence of open cracks, and almost detached blocks respectively. These information on the dynamic properties of a landslide-prone slope could be used in a correct planning of civil infrastructure to minimize the potential risk of building damage in the seismically active Hunza valley.